A REVIEW OF EXPERIMENTAL STUDY OF PV SYSTEM AND PEDAL POWER WITH GRID - Verma, Priyanka; Sharma, A.K. (International Journal of Engineering Technologies and Management Research, 2016)
Through the photovoltaic effect the energy contained in the sunlight can be converted directly into electrical energy. This method of energy conversion presents some advantages, such as: Its modular characteristic offers large flexibility in the design and application of this kind of energy generator. Short time of installation and operation. High reliability, and low maintenance.